Progress of African Americans in higher education attainment: The widening gender gap and its current and future implications. - Kaba, Amadu J. (Education Policy Analysis Archives, 2005)
This research argues that despite all of the obstacles that African Americans have confronted in the history of the United States, they have made substantial progress in higher education attainment from the 1970s to the beginning of the 21st century. It reveals that the rise in attainment of college and university degrees has resulted in a substantial increase in living standards and that African Americans are making important economic, social and political contributions to the United States. I present several reasons why black males are not performing as well as black females in higher education attainment. Analyses are also presented regarding the current and future implications of the growing gap between black males and black females.